Teachers' Influence on Students' Independence in Elementary School - Titin Gustia Widel; Zaka Hadikusuma Ramadan (AL-ISHLAH: Jurnal Pendidikan, 2021)
Teachers' role in moulding the character of primary school students is the focus of this study, as is student behaviour in applying autonomous character ideals in the classroom. Learning and character development can only be achieved via effective teaching. When it comes to shaping pupils into citizens who can serve their country, a teacher plays a crucial role in doing just that. By conducting a survey, this study employs a quantitative descriptive method. This study was carried out in the fourth grade of elementary school. In this study, data was gathered through interviews, observation, a questionnaire, and documentation. Results of this study reveal that the teacher's role in shaping the autonomous character of fourth-grade children is as follows: the teacher is more than just a science teacher; he or she is also in charge of the students' behaviour. Through teaching and learning activities, teachers instil values and character traits in students. Motivators, the teachers' role in helping children to develop character values